The Role of Fault‐Zone Architectural Elements on Pore Pressure Propagation and Induced Seismicity. Issue 3 (11th September 2018) - Ortiz, John P.; Person, Mark A.; Mozley, Peter S.; Evans, James P.; Bilek, Susan L.
Abstract: We used hydrogeologic models to assess how fault‐zone properties promote or inhibit the downward propagation of fluid overpressures from a basal reservoir injection well (150 m from fault zone, Q = 5000 m 3 /day) into the underlying crystalline basement rocks. We varied the permeability of the fault‐zone architectural components and a crystalline basement weathered layer as part of a numerical sensitivity study. Realistic conduit‐barrier style fault zones effectively transmit elevated pore pressures associated with 4 years of continuous injection to depths of approximately 2.5 km within the crystalline basement while compartmentalizing fluid flow within the injection reservoir. The presence of a laterally continuous, relatively low‐permeability altered/weathered basement horizon ( k altered layer = 0.1 × k basement ) can limit the penetration depth of the pressure front to approximately 500 m. On the other hand, the presence of a discontinuous altered/weathered horizon that partially confines the injection reservoir without blocking the fault fluid conduit promotes downward propagation of pressures. Permeability enhancement via hydromechanical failure was found to increase the depth of early‐time pressure front migration by a factor of 1.3 to 1.85. Dynamic permeability models may help explain seismicity at depths of greater than 10 km such as is observed within the Permian Basin, NM. Abstract : Article impact statement : Hydrologic modeling of basal reservoirs shows crystalline basement fault‐zone permeability structures promote deep induced seismic events.